Delaying treatment for peritonitis could be related to longer hospitalization in patients on peritoneal dialysis - Yusaku Koshitori; Nami Takai; Yoshihito Isomura; Tetsuaki Hiramatsu; Yasuhiro Suzuki; Hangsoo Kim; Sosuke Fukui; Masashi Mizuno (Renal Replacement Therapy)
Abstract Background When peritoneal dialysis (PD)-related peritonitis occurs in PD patients, diagnostic and therapeutic approaches should be started as soon as possible. However, medical attention may be delayed in patients experiencing minimal symptoms with cloudy PD fluid (PDF). This study investigated differences between the first and later episodes of peritonitis and relationships between interval from peritonitis onset to attending hospital and both duration of hospitalization and medical expenses. Methods We retrospectively investigated 36 patients with multiple episodes of PD-related peritonitis among 125 patients receiving PD therapy from January 2016 during a 6-year period at a single center. Results In 50 episodes of PD-related peritonitis among outpatients, median interval from recognition of cloudy PDF to hospital visit was 4.0 h (interquartile range [IQR] 2.0–12.0 h). With the first episode of peritonitis, the median interval was 8.5 h (IQR 3.6–18.0 h), improving to 2.0 h (IQR2.0–3.3 h) with second and subsequent episodes of peritonitis after patients were provided with education in PD-related issues. Median duration of hospitalization associated with PD-related peritonitis was 16.0 days (IQR 14–22 days) when the interval to hospital visit was < 6 h, significantly shorter than the 20 days (IQR 16–39 days) when the interval from the patient recognizing peritonitis to hospital visit was ≥ 6 h. Conclusions Our results suggest that delaying the hospital visit might lead to longer duration of hospitalization, suggesting that effective educational approaches might be warranted to change behaviors during initial peritonitis.